Moral Responsibility for Consequences of One’s Own Death: An Illustrative Analysis - Rudnick, Abraham (Advances in Social Sciences Research Journal, 2021)
This paper addresses what (if at all) is the moral responsibility of a person for consequences of their own death, and what (in)actions may be morally required of that person in order to try to optimize the balance of negative and positive consequences of their future death. Illustrative analysis using chance, choice and constraint as necessary and arguably jointly sufficient considerations is used. It concludes that a capable person’s moral responsibility extends after that person’s death, and that some (in)actions are morally required of the person while they are alive to try to optimize their death’s consequences to others.